Anesthesia of thoracic surgery in children. Issue 4 (26th February 2018) - Semmelmann, Axel; Kaltofen, Heike; Loop, Torsten
Summary: Providing anesthesia in children with thoracic disease is a challenging task. The effects of the underlying disease, the surgical interventions, and preexisting condition of the patient need to be considered when planning perioperative care. The perioperative care for children undergoing thoracic surgery requires specific techniques adapted to the pediatric physiology and anatomy. This review is focused on anesthetic strategies for thoracic surgery with an emphasis on perioperative analgesia including neuraxial techniques.